PERAN PENGAWAS DALAM MENDUKUNG PROGRAM PEMBIASAAN PENDIDIKAN AGAMA ISLAM TINGKAT SEKOLAH DASAR - Tuti Herawati (Balai Diklat Keagamaan Bandung, 2022)
The purpose of this article is to emphasize the importance of practice or habituation, in addition to invoke students to live Islamic way. Habituation of Islamic Religious Education (PAI) in elementary schools is an actualization of student character building since an early age. In addition to teachers, supervisors also have a strategic role for improving the quality of PAI through habituation programs, because they can coordinate directly with two relevant agencies: The Ministry of Religious Affairs and The Education and Cultural Office. The methods used in this study are participatory observation, interviews, and literature review to support the main data. The results show that the role of PAI Supervisors in habituation is to motivate, to facilitate, as well as to be a partner for finding solutions towards the obstacles faced by Islamic Religious Education teachers in schools. It can be concluded that the supervisor as a Quality Assurance of Islamic Religious Education in elementary schools must support teachers to be able to manage the habituation proportionally, to encourage stakeholders, to integrate it with all school elements, and to complement the facilities as well as infrastructures which are still unevenly maintained by the elementary schools.